To evaluate the equation \((3^{-5} \cdot (\sqrt[4]{81})^3) / (3^{-4}) = 3^{-6}\), let's simplify the left side step by step.
-
Simplify \(\sqrt[4]{81}\): \[ 81 = 3^4 \implies \sqrt[4]{81} = \sqrt[4]{3^4} = 3 \] So, \((\sqrt[4]{81})^3 = 3^3 = 27\).
-
Substitute into the equation: \[ 3^{-5} \cdot (3^3) / (3^{-4}) = 3^{-5} \cdot 27 / 3^{-4} \]
-
Convert 27 to a power of 3: \[ 27 = 3^3 \] So the expression becomes: \[ 3^{-5} \cdot 3^3 / 3^{-4} \]
-
Combine using the Product Property: \[ 3^{-5 + 3} / 3^{-4} = 3^{-2} / 3^{-4} \]
-
Apply the Quotient Property: \[ 3^{-2 - (-4)} = 3^{-2 + 4} = 3^2 \]
The left side simplifies to: \[ 3^2 \]
Now compare that to the right side \(3^{-6}\): Since \(3^2 \neq 3^{-6}\), the original equation is false.
Final Answer: False. There is an error in calculation using the Quotient Property.